Energy storage in energy markets : uncertainties, modelling, analysis and optimization - Mohammadi-Ivatloo, Behnam; Mohammadpour Shotorbani, Amin; Anvari-Moghaddam, Amjad (United Kingdom : Academic Press, 2021)
'Energy Storage in Energy Markets reviews the modeling, design, analysis, optimization and impact of energy storage systems in energy markets in a way that is ideal for an audience of researchers and practitioners. The book provides deep insights on potential benefits and revenues, economic evaluation, investment challenges, risk analysis, technical requirements, and the impacts of energy storage integration. Heavily referenced and easily accessible to policymakers, developers, engineer, researchers and students alike, this comprehensive resource aims to fill the gap in the role of energy storage in pool/local energy/ancillary service markets and other multi-market commerce. Chapters elaborate on energy market fundamentals, operations, energy storage fundamentals, components, and the role and impact of storage systems on energy systems from different aspects, such as environmental, technical and economics, the role of storage devices in uncertainty handling in energy systems and their contributions in resiliency and reliability improvement'--
Includes bibliographical references and index.
Keywords: Energy storage